Bioinformatics Application in Search of Phylogenetic Relationship on Eleven Species of Phalaenopsis Blume (Orchidaceae) Based on Gen Internal Transcribed Spacer (ITS1 AND ITS2), 5.8 DNA Ribosomal - Rindyastuti, Ridesti (Proceeding International Conference on Global Resource Conservation, 2013)
Bioinformatics are a reliable method to trace biological information in the molecular level including the analysis of molecular phylogeny relationship of species. This paper discuss about the phylogeny relationship of eleven species of Phalaenopsis (Orchidaceae) based on internal transcribed spacer (ITS1 and ITS2) gene, 5.8 ribosomal DNA by bioinformatics applications. The method of this study is a database search in Gene Bank through the NCBI website (http://www.ncbi.nlm.nih.gov) to search nucleotide data and DDBJ (http//www.ddbj.nig.ac. jp) for the use of software BLAST and the EBI (http://www.ebi.ac.uk) for nucleotide alignment of similarity search. Cladogram shows that P. javanica and P. patherina have a very close relationship. Both species are also still closely related to P. cornu-cervii. Species P. modesta, P. tetraspis and P. lueddemannian are separated each other that can be revealed to have distant phylogenetic relationship than other species in the genus. Species P. amboinensis form a cluster with the species P. floresensis and P. mannii. However, P. sumatrana was closely related to P. corningiana. The cladogram showed that formation among Phalaenopsis species was not apparently grouping. Moreover, there is a large group consisting of P. amboinensis, P. Sumatrana, P. cornu-cervi, P. pantherina, P. floresensis, P. mannii and P. corningiana, while P. modesta, P. tetraspis and P. lueddemanniana were not clustered into the group.Keywords: Bioinformatics, phylogenetic relationship, Phalaenopsis, databases, internal transcribed spacer (ITS) gene.